Certificação Participativa e Agroecologia: Processos de Organização e Resistência Camponesa na Mata Paraibana. - Oliveira, Mariana Borba de (2012)
The topic approached by this research deals in a general way with the rural resistance against the modern agriculture being this a resistance to a form of production and consumption purely capitalist that considers food as merchandise and thus spreads the social and environment chaos. Under this perspective, we interpret a peasant organization whose production is in a agroecologic basis and the commercialization of the products is done straight to the consumers in a public fair as a strong strategy of resistance that allows the (re)construction of the basis of the rural reproduction and the construction of paradigms that generate a local development. We have investigated the hypothesis of this experience to be fortified by a mechanism of certification developed by the social movement linked to Agroecology what means a participative certification for agroecologic products. The experience studied is the Agroecologic Fair that take place in João Pessoa-PB, in the campus I of the UFPB, that commercialize horti/fruit/farm products coming from 4(four) rural settlements located in Várzea do Rio Paraiba (alongside Paraiba River) in the district of Cruz do Espirito Santo, Sapé and Sobrado and a rural settlement located in the South Coast of Paraiba district of Conde. We evidenced that the strength of the related experience is achieved at the moment that a process of certification is granted to the agroecologic products through a common effort of production control that involves producers, consumers, technicians, government and civil society.